FACING THE PROBLEM OF COMMON ERRORS BY LEARNERS - Xurramova, Feruza (Журнал иностранных языков и лингвистики, 2021)
Error analysis came as an alternative approach and took the place of dominant approach contrastive analysis. This article deals with the issues on the common problems faced by language learners and their probable solutions.